2013
DOI: 10.4103/2230-8210.117196
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes of female patients with congenital adrenal hyperplasia due to 21-hydroxylase defi ciency

Abstract: Fertility in women with congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD) appears to be reduced, especially in women with the classic salt-wasting type. Several factors have been suggested to contribute to this subfertility such as androgen excess, adrenal progesterone hypersecretion, consequences of genital reconstructive surgery, secondary polycystic ovaries syndrome, and psychosexual factors. In contrast to this subfertility, pregnancies are commonly normal and uneventful. Adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Mansourian [ 30 ] and Mnif et al . [ 11 ] found that pathologic hormonal profiles of women with hyper- and hypothyroidism often result in abortions, low birth weight and premature labor. In our study, we did not find any association between mutations in the CYP21A2 gene and the presence of thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mansourian [ 30 ] and Mnif et al . [ 11 ] found that pathologic hormonal profiles of women with hyper- and hypothyroidism often result in abortions, low birth weight and premature labor. In our study, we did not find any association between mutations in the CYP21A2 gene and the presence of thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal androgens directly inhibit aromatase activity in granulosa cells of the ovary, thus indirectly hindering foliculogenesis. The high androgen levels result in gonadotropin-releasing hormone (GnRH), inhibition, leading to anovulation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the full range of genital anomalies includes complete fusion of the labioscrotal folds and a phallic urethra, partial fusion of the labioscrotal folds, precocious pubarche, clitoromegaly with a shallow vagina, as well as accelerated growth and skeletal maturation [5, 6]. Hirsutism, oligomenorrhea, and infertility are consequences later we face in life [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, fertility, rather than pregnancy rates, seems to be reduced compared with the general population. Subfertility in females with classic CAH is due to several contributing factors, including androgen excess, adrenal progesterone hypersecretion, consequences of genital reconstructive surgery, secondary polycystic ovaries syndrome, ovarian adrenal rest tumors, and psychosexual factors (6).…”
mentioning
confidence: 99%